Geographic distribution and abundance of the Afrotropical subterranean scale insect Stictococcus vayssierei (Hemiptera: Stictococcidae), a pest of root and tuber crops in the Congo basin. Issue 2 (1st April 2020) - Doumtsop, Armand R. P. F.; Hanna, Rachid; Tindo, Maurice; Tata-Hangy, Willy K.; Fotso, Apollin K.; Fiaboe, Komi K. M.; Fomena, Abraham; Kemga, Adolph; Normark, Benjamin B.
Abstract: Stictococcus vayssierei is a major pest of root and tuber crops in central Africa. However, data on its ecology are lacking. Here we provide an updated estimate of its distribution with the aim of facilitating the sustainable control of its populations. Surveys conducted in nine countries encompassing 13 ecological regions around the Congo basin showed that African root and tuber scale was present in Cameroon, Central African Republic, Congo, Democratic Republic of Congo, Equatorial Guinea, Gabon and Uganda. It was not found on the sites surveyed in Chad and Nigeria. The pest occurred in the forest and the forest-savannah mosaic as well as in the savannah where it was never recorded before. However, prevalence was higher in the forest (43.1%) where cassava was the most infested crop, compared to the savannah (9.2%) where aroids (cocoyam and taro) were the most infested crops. In the forest habitat, the pest was prevalent in all but two ecological regions: the Congolian swamp forests and the Southern Congolian forest-savanna mosaic. In the savannah habitat, it was restricted to the moist savannah highlands and absent from dry savannahs. The scale was not observed below 277 m asl. Where present, the scale was frequently (87.1% of the sites) attended by the ant Anoplolepis tenella . High densities (>1000 scales per plant) were recorded along the Cameroon–Gabon border. Good regulatory measures within and between countries are required to control the exchange of plant materials and limit its spread. The study provides information for niche modeling and risk mapping.